(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Diabetes is a group of chronic diseases characterized by high blood sugar. Modern medicine utilizes a wide range of lifestyle and pharmaceutical interventions aimed at preventing and controlling hyperglycemia. In addition to ensuring proper delivery of glucose to the body's tissues, diabetes treatment aims to reduce the potential for high blood sugar to damage body tissues. Protecting the body from high blood sugar. The importance of this cannot be overemphasized. Direct and indirect effects on the human vascular system are major causes of morbidity and mortality in type 2 diabetes. In general, the adverse effects of hyperglycemia are divided into macrovascular complications (coronary artery disease, peripheral artery disease, and stroke). In this study we are aimed at studying the development of Macrovascular complication among the diabetic and pre diabetic patients visiting a Tertiary care hospital over a period of 1 year as a cross sectional study from the initial date of assessment at 6 months interval.